The impact of contextualization on immersion in healthcare simulation. Issue 1 (January 2016) - Engström, Henrik; Andersson Hagiwara, Magnus; Backlund, Per; Lebram, Mikael; Lundberg, Lars; Johannesson, Mikael; Sterner, Anders; Maurin Söderholm, Hanna
Abstract Background The aim of this paper is to explore how contextualization of a healthcare simulation scenarios impacts immersion, by using a novel objective instrument, the Immersion Score Rating Instrument. This instrument consists of 10 triggers that indicate reduced or enhanced immersion among participants in a simulation scenario. Triggers refer to events such as jumps in time or space (sign of reduced immersion) and natural interaction with the manikin (sign of enhanced immersion) and can be used to calculate an immersion score. Methods An experiment using a randomized controlled crossover design was conducted to compare immersion between two simulation training conditions for prehospital care: one basic and one contextualized. The Immersion Score Rating Instrument was used to compare the total immersion score for the whole scenario, the immersion score for individual mission phases, and to analyze differences in trigger occurrences. A pairedt test was used to test for significance. Results The comparison shows that the overall immersion score for the simulation was higher in the contextualized condition. The average immersion score was 2.17 (sd = 1.67) in the contextualized condition and −0.77 (sd = 2.01) in the basic condition (p < .001). The immersion score was significantly higher in the contextualized condition in five out of six mission phases. Events that might be disruptive for the simulation participants' immersion, such as interventions of the instructor and illogical jumps in time or space, are present to a higher degree in the basic scenario condition; while events that signal enhanced immersion, such as natural interaction with the manikin, are more frequently observed in the contextualized condition. Conclusions The results suggest that contextualization of simulation training with respect to increased equipment and environmental fidelity as well as functional task alignment might affect immersion positively and thus contribute to an improved training experience.